A Retrospective Analysis of Biological Complications of Dental Implants. (12th August 2022) - Atieh, Momen A.; Almutairi, Zainab; Amir-Rad, Fatemeh; Koleilat, Mohammed; Tawse-Smith, Andrew; Ma, Sunyoung; Lin, Lifeng; Alsabeeha, Nabeel H. M.
Abstract : Background and Objective . Several risk factors have been implicated in onset and development of peri-implant diseases. The impact of these factors, however, remains controversial across the different clinical settings and populations. The aim of this retrospective study was to evaluate the risk factors for peri-implant diseases among an Emirati population. Methods . A retrospective analysis of patients aged ≥18 years and having dental implants placed at Dubai Health Authority in 2010. Relevant information related to systemic-, patient-, implant-, site-, surgical- and prosthesis-related factors were collected. The strength of association between the prevalence of peri-implant mucositis and peri-implantitis and each variable was measured by chi-square analysis. A binary logistic regression analysis was performed to identify possible risk factors. Results . A total of 162 patients with 301 implant-supported restorations were included in the study. The age of the patients ranged between 19 and 72 with a mean age of 46.4 ± 11.7 years. The prevalence of peri-implant mucositis at the patient and implant levels were 44.4% and 38.2%, respectively. For peri-implantitis, the prevalence at the patient level was 5.6%, while the prevalence at the implant level was 4.0%. The binary logistic regression identified three risk factors (smoking habits, histories of treated periodontitis and lack of peri-implant maintenance) for peri-implantitis. Conclusion . Within the limitations of this study, smoking habits, history of treated periodontitis and lack of peri-implant maintenance were significant risk factors for peri-implantitis. Early detection of these factors would ensure appropriate planning and care of patients at high risk of developing peri-implant diseases.